ANALISIS DAN SIMULASI MODEL SUSCEPTIBLE INFECTIVE TREATMENT RECOVERY PADA PENYEBARAN PENYAKIT MALARIA DI KOTA MEDAN - Eka Yusnita; Machrani Adi Putri Siregar (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Malaria is an infectious disease caused by plasmodium, which is a single-celled living creature belonging to the group of protozoan parasites, malaria is transmitted through the bite of a female Anopheles mosquito containing plasmodium in it. Plasmodium carried through mosquito bites will live and reproduce in human red blood cells. This disease attacks all age groups, both men and women. People who are exposed to malaria will have symptoms of fever, chills, sweats, headaches, nausea or vomiting. Patients who show clinical symptoms must undergo laboratory tests to confirm their positive malaria status. The purpose of this study was to determine the model of the spread of Malaria and to analyze the stability of the model of Malaria. This study uses the SITR mathematical model which involves 4 population compartments, namely Susceptible (S), Invective (I), Treatment (T), Recovery (R). The data used is secondary data obtained from the Medan City Health Office through the Medan City Health Office. From this study, the SITR mathematical model was obtained, two equilibrium points, namely the point of disease and endemic from the SITR model with a basic Reproductive value of = 0, 2693449588 or  < 1. The greater the basic reproduction number, the more likely it is that malaria will spread, but the more the smaller the basic reproduction number, the smaller the chance for malaria to spread and will gradually disappear